2021
DOI: 10.1136/oemed-2020-107345
|View full text |Cite
|
Sign up to set email alerts
|

Associations between workplace characteristics and ‘outness’ in LGBTI workers in Austria

Abstract: ObjectivesLesbian, gay, bisexual, transgender and intersex (LGBTI) individuals are often subjected to negative attitudes in the workplace, which may lead to non-disclosure of their sexual orientation and/or gender identities. We aimed to determine the prevalence of workplace disclosure of sexual or gender identity (ie, ‘outness’; being ‘out’) and to examine its associations with workplace characteristics in LGBTI workers in Austria.MethodsThis cross-sectional study analysed sociodemographic, work-related and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
4
0
3
Order By: Relevance
“…Plurisexual minorities may experience stigma and discrimination from both heterosexuals and monosexual sexual minorities (Alarie & Gaudet, 2013; Friedman et al, 2014). Some research suggests that plurisexual employees are less likely to disclose their sexual minority identity than are monosexual employees (Corrington et al, 2019; Markovic et al, 2022) and that they also report higher rates of substance use (Demant et al, 2017). Given the limited research on the specific workplace experiences of plurisexual individuals (e.g., Bayrakdar & King, 2022; Kuyper, 2015) and the value of avoiding uniformity assumptions about sexual minority group members, we included plurisexual status as a variable within the present study.…”
Section: A Social Cognitive Perspective On Sexual Identity Management...mentioning
confidence: 99%
“…Plurisexual minorities may experience stigma and discrimination from both heterosexuals and monosexual sexual minorities (Alarie & Gaudet, 2013; Friedman et al, 2014). Some research suggests that plurisexual employees are less likely to disclose their sexual minority identity than are monosexual employees (Corrington et al, 2019; Markovic et al, 2022) and that they also report higher rates of substance use (Demant et al, 2017). Given the limited research on the specific workplace experiences of plurisexual individuals (e.g., Bayrakdar & King, 2022; Kuyper, 2015) and the value of avoiding uniformity assumptions about sexual minority group members, we included plurisexual status as a variable within the present study.…”
Section: A Social Cognitive Perspective On Sexual Identity Management...mentioning
confidence: 99%
“…Given the high prevalence of workplace violence experienced by TNB workers, employers in the conventional workforce can incorporate elements specific to gender identity-based workplace violence into their violence prevention programmes, including training, written antidiscrimination policies, policies that encourage reporting, identifying and training allies to on June 26 27 A study in Austria found that lesbian, gay, bisexual, transgender and intersex (LGBTI) workers were more likely to be out in the workplace if their employer fostered an LGBTIfriendly work environment and if there were antidiscrimination provisions in their labour contracts. 28 In the USA, TNB workers are further protected by Title VII of the Civil Rights Act of 1964, which prohibits employment-related discrimination or harassment based on sex; 'sex' includes both gender identity and sexual orientation following the 2020 Bostock v Clayton County Supreme Court decision. 29 For workers in the street economy, broader legal and societal interventions have been recommended to prevent gender identity-based workplace violence, including decriminalisation of sex work, educational interventions to reduce transphobia and social policies to improve economic opportunities for TNB people.…”
Section: Workplacementioning
confidence: 99%
“…In this article, we focus on public opinions of discriminating members of the LGBTI community when accessing to the labour market. As mentioned by Frick (2016) and Valfort (2017), LGBTI individuals face extensive discriminations in employment, often characterised by negative attitudes which may result into non-disclosive behaviours of their sexual orientation and/or gender identity (Markovic, et al, 2022). Recent European surveys among gays and lesbians show that an important amount of people experienced discrimination or harassment in the workplace (Frick, 2016).…”
Section: Introductionmentioning
confidence: 99%